Updating the Signal-To Level To Reduce Anti-Hepatitis C Virus False Positivity - Oztürk, S.; Ağalar, C. (Kowsar Medical Institute, 2021)
Background: Anti-hepatitis C virus (anti-HCV) is the only screening test being used in the diagnosis of hepatitis C. In this study, we examined anti-HCV positivity rates in our hospital. Objectives: The aim of administering the anti-HCV test was to distinguish patients with hepatitis C infection from false positivity in patients with reactive results. Methods: The anti-HCV tests were performed at Fatih Sultan Mehmet Training and Research Hospital in Istanbul, Turkey, between January 1, 2015 and December 31, 2019. The patients were evaluated retrospectively in terms of age, gender, anti-HCV titer, the clinic for which the examination was requested, the reason for the examination, and the history of hepatitis C. Results: In this study, 511 patients who had two negative polymerase chain reaction (PCR) results were evaluated as false positive cases and enrolled. The cut-off value was found to be 7.5 IU/ml, with the highest sensitivity of 94.4% and specificity of 94.5% (area under the curve [AUC]: 0.982). The lowest anti-HCV titer (5.2) was from patients without acute hepatitis, who were HCV-RNA positive and diagnosed with chronic hepatitis C. Conclusions: It may be more appropriate to report anti-HCV cut-off value of 0-5 as negative, 5-7.5 as borderline, and > 7.5 as positive. Working with a more acceptable cut-off level with a greater number of tests can help identify patients with asymptomatic HCV infection. Also, it can possibly reduce the cost due to a decrease in the number of PCR tests administered. © 2021, Author(s).
Keywords: Anti-Hepatitis C Virus; False Positive; Hepatitis C Virus; S/Co; Signal-To-Cutoff; Co; S